Disagreement in peer interaction: Its effect on learner task performance. (February 2020) - Chen, Wenxue
Abstract: Research on peer interaction has shown that learners working collaboratively in communicative tasks promotes problem-solving and knowledge-building. However, attention has mainly been directed to language-related problem-solving during peer interaction. Little is known about how learners deal with problems other than linguistic issues in their dialogue. The present study examined disagreement in peer communication and its effect on learners' task performance. It compared the peer interaction of learners carrying out two collaborative writing tasks, focusing on their resolution of disagreements and the co-constructed texts. The findings indicated that a collaborative pattern of peer dialogue that encouraged deliberation after disagreement was more likely to result in successful resolution and more precise co-constructed texts. However, interlocutors employing a non-collaborative pattern of interaction failed to fully engage with each other's contributions, so discussions were short and the reconstructed texts tended to be inaccurate. Disagreement itself can prolong peer interaction due to learners' evaluations, reasoning, and explanations, affording more opportunities for practice in the target language and improving their comprehension.